Profitabilitas, Intensitas Aset Tetap, dan Leverage sebagai Penentu Penghindaran Pajak: Bukti Empiris dari Perusahaan Makanan & Minuman yang Terdaftar di IDX 2022-2024 - Iin indarti indarti; Tjandra Tirtono (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of profitability, fixed asset intensity, and leverage on tax avoidance. The approach used in this study is a quantitative approach. The data collection technique used in this study is the documentation method by collecting records of the company's annual report documents and then analyzing them. The number of samples used is 60 annual companies, namely food and beverage companies, so the sampling technique used is sensus sampling. The analysis tool used in the study is multiple linear regression. The results of the study stated that profitability had a negative and significant effect, the intensity of fixed assets, and leverage had no effect on tax avoidance, with a determination coefficient value of 16.8%, meaning that profitability, fixed asset intensity and leverage were able to explain the employee performance variables of 16.8%, . While the remaining 83.2% were explained by other variables besides the variables studied.